Development and Implementation of an Integrated Academic-Behavior Intervention. (September 2022) - Gettinger, Maribeth; Kratochwill, Thomas R.; Foy, Alison; Eubanks, Abigail
The relationship between learning disabilities and behavior disorders is well documented and has led to the development of integrated interventions that target both academic and behavior deficits in elementary school–age students. This paper describes the rationale for, development of and implementation of an integrated academic-behavior intervention called a cademic and behavior combined support ( ABC Support ). The intervention was developed by integrating the critical intervention elements from two single-focus interventions (i.e., repeated reading and check-in/check-out) into a single comprehensive intervention designed to improve reading fluency for early elementary school–age students with reading disorders while also strengthening their engagement and compliance with behavior expectations.